2022
DOI: 10.3390/tropicalmed7120431
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Impact of Climate Change on the Distribution of a Neglected Arboviruses Vector (Armigeres subalbatus) in China

Abstract: The geographic boundaries of arboviruses continue to expand, posing a major health threat to millions of people around the world. This expansion is related to the availability of effective vectors and suitable habitats. Armigeres subalbatus (Coquillett, 1898), a common and neglected species, is of increasing interest given its potential vector capacity for Zika virus. However, potential distribution patterns and the underlying driving factors of Ar. subalbatus remain unknown. In the current study, detailed map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…Moreover, the land use change and human disturbance factors are not taken into account in the modeling process, and these limitations can cause bias in the simulation results. Despite the many assumptions and uncertainties in species distribution simulations, the MaxEnt model is still an important data source tool for species distribution simulation predictions of future suitable areas, which is useful for proposing and developing scientific adaptation strategies based on predicted species distributions to cope with future climate change impacts on species, as well as ecosystem-level biota [67,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the land use change and human disturbance factors are not taken into account in the modeling process, and these limitations can cause bias in the simulation results. Despite the many assumptions and uncertainties in species distribution simulations, the MaxEnt model is still an important data source tool for species distribution simulation predictions of future suitable areas, which is useful for proposing and developing scientific adaptation strategies based on predicted species distributions to cope with future climate change impacts on species, as well as ecosystem-level biota [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…According to the output results of MaxEnt (Figure 4), using the presence probability of 0.23 as the critical condition for the Ginkgo biloba suitable area, the threshold values of the dominant environmental variables are: Bio6, −12.86-6.60 °C; Bio13, 120. 68…”
Section: Main Environmental Variables Affecting the Ginkgo Biloba Sui...mentioning
confidence: 99%
“…The variables used for niche modeling were at a spatial resolution of 0.5 arcminutes (~1 km 2 ). Multi-collinearity among the bioclimatic variables may affect the prediction analysis, as they are mainly derived from temperature and precipitation (Wang et al 2022). Therefore, to avoid multi-collinearity among the variables, a Pearson correlation test was performed using ENMTools v1.4.4 (Warren et al 2010).…”
Section: Environmental Datamentioning
confidence: 99%
“…The maximum entropy model (MaxEnt) is based on the maximum entropy theory, which treats species and their growing environment as a system, determines the stable relationship between species and the environment by calculating the state parameters when the system has maximum entropy, and estimates the distribution of species [27]. Several scholars [28][29][30] have demonstrated that the MaxEnt model is a successful tool for analyzing the potential distribution areas of species, and some have also used species distribution models to predict the potential distribution areas of mosquitoes.…”
Section: Introductionmentioning
confidence: 99%